1998
DOI: 10.1093/humrep/13.suppl_1.196
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study of children born after intracytoplasmic sperm injection (ICSI) with epididymal and testicular spermatozoa and after replacement of cryopreserved embryos obtained after ICSI

Abstract: The aim of this prospective follow-up study of children born after intracytoplasmic sperm injection (ICSI) was to compile data on karyotypes, congenital malformations, growth parameters and developmental milestones in order to evaluate the safety of this new technique. The study design included karyotyping of the parents and their agreement to genetic counselling and prenatal diagnosis and it was based on a physical examination of the child at the Centre for Medical Genetics at the ages of 2 months, 1 year and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 34 publications
0
23
0
2
Order By: Relevance
“…Earlier studies did not fi nd a rise in the malformation rate after ICSI [10,11,30,38,40] . However, the number of cases was either very low or there was no control group or the investigation technique was not performed in a standard fashion.…”
Section: Fetal Malformations After Artmentioning
confidence: 84%
“…Earlier studies did not fi nd a rise in the malformation rate after ICSI [10,11,30,38,40] . However, the number of cases was either very low or there was no control group or the investigation technique was not performed in a standard fashion.…”
Section: Fetal Malformations After Artmentioning
confidence: 84%
“…Several studies have demonstrated that there is no increase in the incidence of congenital anomalies in children born after ICSI compared with standard IVF or with the general population [29][30][31][32][33][34][35][36]. However, others showed that infants born after ICSI might indeed have an excess of major birth defects [37][38][39] and an increased incidence of chromosomal abnormalities [31,35]. It is possible that the increases in congenital abnormalities observed in some ICSI children, such as hypospadias or sex chromosome abnormalities, are due to factors related to paternal infertility and the use of suboptimal male gametes.…”
Section: Discussionmentioning
confidence: 99%
“…32 Bonduelle and colleagues 33 found that the sex ratio of children born after intracytoplasmic sperm injection (ICSI) with testicular or epididymal spermatozoa was modified to 0·40 and 0·60, for males and females, respectively. Additional data from Bonduelle (personal communication) show a significant difference (p=0·05).…”
Section: Discussionmentioning
confidence: 99%